A human rights approach to understanding provider knowledge and attitudes toward the human papillomavirus vaccine in São Paulo, Brazil - Meredith H. Kruse; Robert A. Bednarczyk; Dabney P. Evans (Papillomavirus Research, 2020)
Objective: To determine the extent to which human rights considerations influence the attitudes of healthcare providers in Brazil with regard to access to the human papillomavirus (HPV) vaccine for females over 13 and males of all ages. Methods: From May to August 2015, we conducted a cross-sectional study among healthcare providers in eight public health clinics in the city of Mauá, Brazil. Frequency analysis was conducted across three subject areas: access, knowledge, and attitudes. Results: A total of 154 surveys were analyzed. Providers reported their perception that Brazilians do not have equal access to health (80%) and the vaccine exclusions limit an individual's right to health (72%). Providers stated it is medically effective to vaccinate females over the age of 13 (77%), these females should be vaccinated (84%), and they would vaccinate them (82%). Similar responses were reported for males. Conclusion: Cervical cancer is the 4th leading cause of cancer among females in Brazil. Most cervical cancer cases are caused by persistent HPV infection, preventable through HPV vaccination. Limiting access to the HPV vaccine when medically efficacious is a perceived infringement of an individual's right to health. Brazil has a constitutional responsibility to reduce these access barriers.